Ethical-Religious Seduction: Laplanche and Kierkegaard on the Priority of the Other - Kline, Peter (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2025)
This essay offers a psychoanalytic perspective on ethics utilizing Jean Laplanche and Søren Kierkegaard. It proposes a homology between Kierkegaard’s "God" and Laplanche’s "primal adult" as well as between Kierkegaard’s account of the indirection of love and the role of the analyst in the transference relationship. Both Kierkegaard and Laplanche center scenes of second-person relation in which a seductive asymmetry calls forth a rigorous ethics of unknowing.